Local Vessels and Imported Copies Manufactured in Sandy Fabrics at Tell El-Ghaba, North Sinai - Lupo, Silvia Alicia (2013)
This study examines Egyptian ceramic production in the Eastern Delta, particularly several vessels manufactured in marl fabrics attributed to Marl F found at Tell el Ghaba, a Saite settlement on the eastern border. A characterisation of TG 12, TG 14, and TG 55/60 fabrics performed under binocular lens is presented, as well as a description of their morphological and decorative repertoire. It is suggested that these sandy fabrics can be closely tied to the Marl F group, as they reflect a technological tradition in pottery production typical of the Eastern Delta and North Sinai that may have persisted from the Second Intermediate Period until at least the Saite period. The fabric typology shows the production of local shapes, along with imitations of imported vessels from the Levant and Cyprus different from those previously recognised in older sites.